Learning to Think for Ourselves and the Work of Sociology - Ilaria Pitti; Patricia Hill Collins (Sociologica, 2025)
In this wide-ranging conversation with Ilaria Pitti, Patricia Hill Collins retraces the interplay between her personal biography and intellectual trajectory. She reflects on the evolution of intersectionality — its promise, risks of depoliticisation, and practical uptakes — while insisting that social-justice ethics remain central. The dialogue also explores “othermothering” as a historically Black, collective-care practice that can inform contemporary struggles in historical times marked by loss and powerlessness. Throughout, Collins positions sociology as a “border discipline” uniquely equipped to analyse structural power, cultivate reflexivity, and foster social change.